1907
DOI: 10.1002/ange.19070200107
|View full text |Cite
|
Sign up to set email alerts
|

Über die Bestimmung der Schwefelsäure durch Benzidin

Abstract: KefF:. ~~" $~~~~ 190,.] Friedheim u. Nydegger : Best. der Schwefelsilure durch Benzidin. 3) Es wird eine Benzidinlosnng, deren Wirkungswert gegen H2S04 bekannt ist, im UberschuR zu der Losung des Sulfates gegeben, der Niederschlag abfiltriert und ein aliquoter Teil des Filtrates diazotiert. C,,H,(NH,),, 2HC1 + 2NaN0, = 2N, + C,,H,(OH), + 2NaC1 + 2H,O. Der Stickstoff wird gemessen uud so der Uber-schuR der zugesetzten Benzidinlosung, also auch das zur Umsetzung der Schwefelsaure vcrbrauchte Volumen ermittelt. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1911
1911
1947
1947

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Other investigators have hydrolyzed with 1 or 2 A sulfuric or hydrochloric acid (10, IS). Melnick et al (6) showed, however, that the vitamin Bt content of a dried yeast sample hydrolyzed with 2 N sulfuric acid was much lower than the value obtained when 0.055 N acid was used for the hydrolysis. They ascribed this to destruction of an acid-labile substance possessing vitamin B« activity.…”
Section: Acknowledgmentmentioning
confidence: 94%
See 2 more Smart Citations
“…Other investigators have hydrolyzed with 1 or 2 A sulfuric or hydrochloric acid (10, IS). Melnick et al (6) showed, however, that the vitamin Bt content of a dried yeast sample hydrolyzed with 2 N sulfuric acid was much lower than the value obtained when 0.055 N acid was used for the hydrolysis. They ascribed this to destruction of an acid-labile substance possessing vitamin B« activity.…”
Section: Acknowledgmentmentioning
confidence: 94%
“…No advantage is gained by allowing precipitation to continue overnight. 6. The precipitate obtained from a sample of semimicro size is too large to be collected in a Fiske filter tube (3,5) or on a filter stick, either of which is quickly clogged by the compacted solid.…”
Section: Table V Recovery Of Cyanidementioning
confidence: 99%
See 1 more Smart Citation
“…The benzidine method is probably the best known example of a filtration method. It has been the subject of extensive investigation (16,20,49,84,109) and the concentrations of impurities (16,17,20,37,56,91,105,109), concentrations of reagents (17), temperature and method of titration (31,37,46,57,90,95,105), and the method of filtration and washing (31,95,119) have all been carefully studied.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The authors' attention was called by V. K. Krieble to several published accounts on the determination of soluble sulfates by the use of benzidine. The method seems first to have been proposed by Midler (19) and was later modified by Raschig (22), von Knorre (l/¿), and Friedheim and Nydegger (7). Subsequent applications of the benzidine method and modifications included the determination of sulfur in biologic liquids (S, 6, 9, IS, 15, 20, 21), rubber (17), organic 1 The preliminary experiments in this investigation were carried out by the senior author in 1920-21 at The Emerson Laboratories, Springfield, Mass.…”
Section: Literature Citedmentioning
confidence: 99%